A Strong Independent (Video Game) Woman Examining Red from Transistor (2014) - Najma Litany Adhyaksana (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2019)
In the 21st century, gender representation in video games has improved as a response to growing criticisms of stereotyped, denigrating portrayals of women. Despite this progress, some of these depictions persist in female characters who appear in the medium, even within the independent (indie) video game scene. Examining Red as the protagonist of the independent role-playing game Transistor (Supergiant Games, 2014) through a semiotic lens, this paper investigates whether her character is in accordance with the prevailing trend of gender representation, especially as it pertains to sexualization and objectification. This paper argues that rather than sexualizing Red, the narrative and visual aspects of Transistor characterize her as a complex, powerful heroine. Moreover, she initially expresses a high level of autonomy in the game, subverting the damsel-in-distress trope. However, she ultimately loses her agency and succumbs to her dependency towards her male lover. As such, Red embodies contradictory concepts of empowerment and helplessness. This indicates that despite originating from an independent studio, the portrayal of Transistor’s protagonist is still in line with the broader paradigm of gender representation in video games. Specifically, it challenges certain harmful stereotypes of women while reaffirming some of them.